The Measurement of Antioxidant Activity of Velvet Beans (Mucuna pruriens) and Velvet Beans (Mucuna pruriens) in Coffee Preparations - Indah Tri Susilowati; Purwati Purwati (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Antioxidant activity tests of methanol extracts of velvet beans (Mucuna pruriens) and velvet beans (Mucuna pruriens) in coffee preparations have been previously carried out by several researchers. This present study aims to examine the phytochemical and antioxidant activities of methanol extracts of Mucuna pruriens and Mucuna pruriens in coffee preparations. The methanol extract was tested for the phytochemical and antioxidant activities by applying DPPH (1,1-Dhiphenyl-2-picrylhydrazil) method. The results of the phytochemical test showed that the methanol extracts of the Mucuna pruriens and Mucuna pruriens in coffee preparations contained secondary metabolites of flavonoids, alkaloids, saponins, terpenoids, and tannins. The outcomes of the antioxidant activity test revealed that the methanol extracts of the Mucuna pruriens and Mucuna pruriens in coffee preparations had antioxidant activities, as indicated by the IC50 values of 42.09 ppm and 37.23 ppm. It was also revealed that the antioxidant content of Mucuna pruriens in coffee preparations was stronger than the content in the velvet beans alone.